Foreign experience of digital business transformation - L. M. Rubaeva; A. A. Datieva (Вестник университета, 2022)
Digital transformation, at present, can be recognized as one of the crisis management tools. Therefore, the relevance of scientific work is manifested in the peculiarities of organisation management in the digitalisation during the COVID-19 pandemic. The subject of the study is the experience of applying digital business transformation in foreign companies. The analysis of new trends in the digital technologies development, as well as their impact on the business processes transformation, taking place in foreign companies has been carried out. The main features of the organisation’s management in the digitalisation during the COVID-19 pandemic have been determined. The scientific novelty lies in the identification and study of the main ways of mastering digital technologies used by foreign organisations during the crisis in order to maintain business competitiveness.